Coverage-dependent adsorption of H2O on dicalcium silicate (1 0 0) surface: A DFT study. (28th February 2022) - Qi, Chongchong; Xu, Xinhang; Wang, Daolin; Feng, Yan; Zhang, Qinli; Chen, Qiusong
Graphical abstract: Highlights: Water adsorption on C2S (1 0 0) surface was investigated by DFT. Single and multi-water adsorption at different coverages was investigated. Adsorption configuration, adsorption energy, electron transfer, PDOS and charge density was analysed. Anti-cooperative molecular adsorption was observed when water coverage ≤ 1. Abstract: Dicalcium silicate (C2 S) is one of the dominating components in Portland cement and is of particular importance for the production of low energy cement. Understanding the interaction between water molecules and C2 S low-index surfaces is a key step for revealing the hydration mechanism of C2 S. Herein, first-principle density functional theory (DFT) calculations were used to analyse the adsorption of water molecules on β-C2 S (1 0 0) surface with different coverage. Considering the reactive Ca sites on β-C2 S (1 0 0) surface, four degrees of water coverage (θ = 1/4, 1/2, 3/4, and 1) were investigated. Adsorption configuration, adsorption energy, electron transfer, partial density of states, and charge density were analysed. Results indicate that the adsorption energy was in the range of −0.70 eV to −0.99 eV, −1.40 eV to −1.93 eV, −2.13 eV to −2.43 eV, and −3.00 eV for 1–4 water molecules adsorption, respectively. The multi-water molecules adsorption was generally anti-cooperative when θ ≤ 1 and the adsorption energy was mainly originated from the surface-water electronic interaction. Molecular adsorption was observed and the adsorption configuration was influenced by the Ca sites. The more the adsorbed water molecules, the more obvious the outward movement and the deeper the adsorption influence into the solid. Electrons were transferred from the surface to water molecules after adsorption. Water molecules became more stable upon adsorption and strong overlapping between water O and surface Ca orbitals was observed.